ATP-sensitive peptide-based coacervates for intracellular delivery of therapeutic oligonucleotides - Vedekhina, Tatiana; Anufriev, Vladislav; Polischuk, Nicole; Malakhova, Elizaveta; Alieva, Sabina; Severov, Viacheslav; Bogomiakova, Margarita; Bobrovsky, Pavel; Varizhuk, Anna (Frontiers in Molecular Biosciences, 2026)
Despite advances in the fields of lipoplexes, metal nanoparticles, and other nucleic acid carriers, intracellular delivery of DNA/RNA therapeutics remains a pressing area of molecular medicine. The existing delivery systems have limitations in terms of stability, efficacy, or toxicity. Peptide-based coacervates have recently emerged as a promising alternative. They offer several advantages, including easy DNA/RNA incorporation, low toxicity, and the ability to penetrate membranes. However, they have one main drawback: inefficient intracellular unpacking. In this study, we present a novel approach to programmed drug release from peptide-based coacervates. We used a previously described intrinsically disordered histidine-rich peptide as a coacervate scaffold and introduced a viral or human protein-derived ATP-responsive module into its sequence. We assembled the coacervates by mixing the resulting peptides with RNA and a model oligonucleotide (ODN), plasmid DNA, or mRNA in a pseudophysiological buffer. The admixtures of labeled peptides and ODN enabled monitoring coacervate formation and dynamics using fluorescence microscopy. The coacervates were relatively stable in ATP-free environments and underwent rearrangements involving the partial release of the ODN in the presence of ATP. The coacervates penetrated HEK293 cells within 4 hours and released the ODN into the cytoplasm within 20 h. They were inferior to the ATP-insensitive (control) peptide in delivery assays with plasmid DNA and mRNA but outperformed the control peptide in assays with the ODN. Our preliminary results suggest that ATP-sensitive coacervates have potential as ODN carriers.